2010
DOI: 10.1002/cjoc.201090078
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of Methylene Blue and Rhodamine B on Natural Zeolite: Thermodynamic and Kinetic Studies

Abstract: A batch system was applied to study the adsorption behavior of methylene blue (MB) and rhodamine B (RB) in single and binary component systems on natural zeolite. In the single component systems, the zeolite presents higher adsorption capacity for MB than RB with the maximal adsorption capacity of 7.95×10 -5 and 1.26×10 -5 mol/g at 55 ℃ for MB and RB, respectively. Kinetic studies indicated that the adsorption followed pseudo-secondorder kinetics and could be described by a two-step diffusion process. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Similar effects have been reported for BiPO 4 /BiOBr, Cu 2 O/BiOBr, g- C3N4 /BiOBr, and BiOBr/BiOI heterostructures . MB + adsorption on the Br/Mo heterostructures reaches equilibrium after about 60 min, which is significantly higher than that for some other adsorbents. , …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Similar effects have been reported for BiPO 4 /BiOBr, Cu 2 O/BiOBr, g- C3N4 /BiOBr, and BiOBr/BiOI heterostructures . MB + adsorption on the Br/Mo heterostructures reaches equilibrium after about 60 min, which is significantly higher than that for some other adsorbents. , …”
Section: Resultssupporting
confidence: 81%
“…52 MB + adsorption on the Br/Mo heterostructures reaches equilibrium after about 60 min, which is significantly higher than that for some other adsorbents. 53,54…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption data were simulated by models of Langmuir and Freundlich isotherms. It is found that the data fit the Langmuir adsorption isotherm better (SI Table S3), with the linear coefficient R 2 values closer to 1 . Furthermore, the Langmuir model is served to estimate the maximum MCs uptake values.…”
Section: Resultsmentioning
confidence: 92%
“…It is found that the data fit the Langmuir adsorption isotherm better (SI Table S3), with the linear coefficient R 2 values closer to 1. 39 Furthermore, the Langmuir model is served to estimate the maximum MCs uptake values. The saturated adsorption capacities for MC-LR are 4.80 and 5.99 mg g −1 at 10 Compared with other silica-based adsorbents reported in earlier papers, 16,17 the ordered mesoporous silica SBA-15 exhibits much higher adsorption capacity for MCs.…”
Section: Environmental Science and Technologymentioning
confidence: 99%